ANALISIS PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP LOYALITAS PELANGGAN DI USAHA MINUMAN RINGAN BUBBLE’KU BUBBLE DRINK DAN ICE BLEND DI RAMAYANA DEPT. STORE KOTA SUKABUMI - Deri Firmansyah; Asep Suryana; Dwinanto Priyo Susetyo; Asep Achmad Rifa’i (Jurnal Mirai Management, 2020)
The population in this study were all customers of BUBBLE'KU Bubble Drink and Ice Blend at Ramayana Dept. Store Kota Sukabumi for as long as June as many as 900 people, the sample used in this study was to use the Slovin formula approach, so that a sample of 90 people was taken at random. To test the analysis of research instruments used validity, reliability and classic assumption tests, then for statistical analysis and relationship analysis the Pearson product moment correlation was used, the coefficient of determination, multiple linear regression and to test the hypothesis the t test and F test were used. Based on the results of research that has been done, it can be seen that simultaneously product quality and price significantly influence customer loyalty. By comparing Fcount with ttable (82.536 > 3.10), it means that H0 is rejected and H1 is accepted, and H0 is rejected and H2 is accepted, so the research hypotheses proposed in this study prove that product quality and price together (simultaneously) affect the customer loyalty. The contribution of product quality and price to customer loyalty is 65.5%, while the remaining 34.4% is influenced by variables not examined besides product quality and price including marketing strategy, location, promotion, marketing mix, service quality, promotion and so. Keywords: Product Quality, Price, and Customer Loyalty